Entrepreneurship and Economic Empowerment of Small-scale Agro-processors in South Africa: Implications for Small Business Development and Entrepreneurship Research - Benjamin Manasoe; Victor Mbulaheni Mmbengwa; Joseph Nembo Lekunze (An Overview on Business, Management and Economics Research Vol. 2, 2023)
Entrepreneurship has been gaining popularity and attention across the globe as an essential source of economic growth and employment creation. Furthermore, entrepreneurship has increasingly attracted the governments and policy-making institution’s attention in recent years. This chapter’s purpose was to analyse entrepreneurship’s influence on the economic empowerment of small-scale agro-processors in South Africa. This research was carried out in the five provinces of South Africa of Gauteng, Limpopo, North West, Free State and Mpumalanga. Moreover, the study focused on the influence of entrepreneurship on the economic empowerment of small-scale agro-processors in those provinces. A concurrent mixed-methods research design consisting of a semi-structured questionnaire with 503 small-scale agro-processors was conducted. A stratified sampling method was used, and data were analysed using a multiple regression method. The study found that entrepreneurship significantly influences the economic empowerment of small-scale agro-processors compared to resources and infrastructure. The findings of this study may inform policymakers, government agencies and scholars that access to market and transaction costs are essential entrepreneurship parameters which will facilitate the economic empowerment of small-scale agro-processors in South Africa. The key limitation of the study is that the research was only conducted in five provinces of South Africa and secondly, the there is a small-size of the population, which make the results inaccurate because the data is not sufficient.